An analysis of educational innovation culture by a Delphi expert panel - Parejo, José-Luis; Revuelta-Domínguez, Francisco-Ignacio; Guerra-Antequera, Jorge; Ocaña-Fernández, Almudena (Frontiers in Education, 2022)
This paper aims to reflect on educational innovation from the point of view of its representation as an indispensable element within the pedagogical culture of educational centers. We present the current elements that constitute the definition of educational innovation, its dimensions, obstacles, and determining factors that will delimit the institutionalization of the innovation process in education. To achieve this aim, we applied the Delphi technique and formulated questions whose answers were agreed upon in several iterations by 20 experts. The results have been organized into four categories that provide the backbone features of the visions, paradigms, opinions, and relevant pedagogical reflections on the concept of innovation, on the organization and participants in the process of innovation, on the pressures and resistance encountered during the process, and on the promotion and trends of educational innovation. We conclude that the definition of educational innovation requires a reflective yet critical and transformative component and that there is a close relationship between innovation and leadership in educational centers. We highlight the lack of time and weak training as the main factors limiting the implementation of reflective and transformative educational innovation processes. Finally, we highlight that promoting an educational innovation culture should be based on flexible research and evaluation processes that enable decision-making and favor pedagogical beliefs for change, together with continuous collaborative support.